Pengaruh Pengetahuan Kewirausahaan dan Self Efficacy terhadap Minat Berwirausaha pada Mahasiswa Pendidikan Ekonomi Stambuk 2021 Universitas Negeri Medan - Muamar Rinaldi; Harrington B. Silaban; Laura Magdalena Tambunan; 4Maria Audina Rumapea; Regina Laurensia Br. Ginting; Rossi Dearni Lingga; Teresia Reginanta Ginting (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Students who understand entrepreneurship courses will develop an attitude to achieve achievements, which arises from confidence in themselves. Positive self-confidence is an important element in achieving success and creating satisfaction in line with the knowledge gained. Realizing the importance of students' personal factors, the researcher is interested in exploring the level of students' self-efficacy towards entrepreneurship courses. This study uses a quantitative research method with a causal associative approach, which aims to determine the causal relationship between independent variables (entrepreneurial knowledge and self-efficacy) and dependent variables (entrepreneurial interest). The population in this study is 80 students of the 2021 Stambuk Economic Education at the State University of Medan. The sampling technique used the stratified random sampling method, using the Slovin formula with a significance level of 5%, then the number of samples obtained was 67 people. The results of the study show that entrepreneurial knowledge has a positive and significant influence on students' interest in entrepreneurship. The regression coefficient was 0.527 with a significance value of p = 0.000 (p < 0.05) shows that students who have a better understanding of entrepreneurship tend to have a higher interest in starting a business. Self efficacy, or students' confidence in their ability to achieve goals, does not have a significant influence on entrepreneurial interest. This can be seen from the regression coefficient value of 0.063 and the significance value of p = 0.491 (p > 0.05). This means that even though there is a The positive relationship between self-efficacy and interest, the level of student confidence is not strong enough to directly increase the interest in entrepreneurship. Simultaneously, entrepreneurial knowledge and self-efficacy contribute to students' interest in entrepreneurship. Based on the multiple linear regression test, the model shows that these two variables together can explain the variation in entrepreneurial interest. However, the dominant contribution comes from entrepreneurial knowledge, because this variable has a more significant influence than self-efficacy.